Analisis Kinerja Keuangan Berdasarkan Metode Economic Value Added (Eva) - Muhammad Yunus (Tangible Journal, 2019)
This research was aimed at analysis the performance of Cements Company which listed at BEI, using conventional methods that Economic Value Added (EVA) approach. This research is quantitative descriptive study using secondary data that the financial statements in the period 2016-2019 of Cement Companies listed on the Stock Exchange, this study uses analysis tools such as descriptive analysis, time series analysis, and cross-sectional analysis approach. The results of this study are cements company performance as measured Economic Value Added (EVA) Approach produces a positive value, with growth in Economic Value Added (EVA) every year for each of the cement companies are fluctuative. In cross sectional analysis approach SMGR achieve that the highest average value of EVA afford obtained by INTP, each by 28 percent, Rp973 and Rp3, 326.919.